WATER RESERVES OF WATER RESERVOIRS OF KASHKADARYA REGION AND ISSUES OF THEIR EFFICIENT USE - Suyarkulov Nizamiddin Makhmatkulovich (American Journals Publishing, 2023)
This article covers water resources of Kashkadarya region reservoirs and their future use. The article also talks about economic mechanisms of using regional water reservoirs and issues of water saving.
Keywords: Reservoir, water resources, water saving, economic mechanisms, irrigation.